2014
DOI: 10.1016/j.clim.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Class I and II histone deacetylase inhibition by ITF2357 reduces SLE pathogenesis in vivo

Abstract: We sought to determine if a specific class I and II HDAC inhibitor (ITF2357) was able to decrease disease in lupus-prone NZB/W mice through regulation of T cell profiles. From 22 - 38 weeks-of-age, NZB/W and non-lupus NZW mice were treated with ITF2357 (5 mg/kg or 10 mg/kg), or vehicle control. Body weight and proteinuria were measured every 2 weeks, while sera anti-dsDNA and cytokine levels were measured every 4 weeks. Kidney disease was determined by sera IgG levels, immune complex deposition, and renal path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 61 publications
4
38
0
Order By: Relevance
“…To determine the level of HDAC6 activity in BM, splenic, and glomerular cells from MRL/lpr and C57BL/6 mice, HDAC6 protein was immunoprecipitated as previously published[28]. The immunoprecipitated protein was normalized using the Bradford protein assay then subjected to the HDAC activity assay.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the level of HDAC6 activity in BM, splenic, and glomerular cells from MRL/lpr and C57BL/6 mice, HDAC6 protein was immunoprecipitated as previously published[28]. The immunoprecipitated protein was normalized using the Bradford protein assay then subjected to the HDAC activity assay.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with ITF2357 decreased the IL17 level and increased the percentage of Treg cells through elevating FOXP3 acetylation [Regna et al, 2014]. An increased number of Treg cells may reduce autoantibody production [Regna et al, 2014]. Given the improvement in the similar diseases mentioned above, ITF2357 may have a therapeutic benefit in SLE.…”
Section: Drugs Targeting the Major Components Of The Epigenetic Mechamentioning
confidence: 99%
“…ITF2357 is a hydroxamic acid-derived compound, which is a specific class I and II HDAC inhibitor. Treatment with ITF2357 decreased the IL17 level and increased the percentage of Treg cells through elevating FOXP3 acetylation [Regna et al, 2014]. An increased number of Treg cells may reduce autoantibody production [Regna et al, 2014].…”
Section: Drugs Targeting the Major Components Of The Epigenetic Mechamentioning
confidence: 99%
“…The inhibition of histone deacetylase can upregulate B-cell microRNAs (miRNAs) that silence AICDA/Aicda (AID) and PRDM1/Prdm1 (Blimp-1), contributing to B-cell differentiation processes that underpin antibody and autoantibody responses in lupus MRL/Faslpr/lpr mice (32). HDAC inhibitors are also able to ameliorate renal lesions in lupus nephritis (LN) (33). A clinical study also showed that mycophenolic acid could upregulate the level of histone H3/H4 global acetylation by regulating HATs and HDACs in lupus CD4 + T cells and affected the histone H4 acetylation and histone H3K4 tri-methylation levels in the CD40L promoter region that inhibited the expression of CD40L, which indicates the potential epigenetic mechanism of therapeutic effects in SLE (34).…”
Section: Histone Modifications and Slementioning
confidence: 99%